Metabolic Implications of Surgical Fat Removal: Increase of Adiponectin Plasma Levels After Reduction Mammaplasty and Abdominoplasty. Issue 6 (June 2016) - Vinci, Valeriano; Valaperta, Serenella; Klinger, Marco; Montanelli, Alessandro; Specchia, Claudia; Forcellini, Davide; Maione, Luca; Klinger, Francesco Maria; Caviggioli, Fabio
Abstract : Abstract: Recent studies tried to identify new indicators of risk in the development of insulin resistance, cardiovascular disease, and metabolic syndrome; recently, breast size has been proposed as a new measure of risk for type 2 diabetes mellitus in women. To understand the role of breast adipose tissue and subcutaneous adipose tissue in lipidic and glucose metabolism, we decided to evaluate the variation on levels of adiponectin in plasma and other well-known metabolic markers before and after surgical fat reduction. We formed 2 groups: breast reduction group (M−) and abdominoplasty group (ADD). For all patients enrolled in the study, we recorded anthropometric measurements 1 hour before surgery (that we considered as time zero). At time zero, we always performed a blood sample to observe the assay of glucose, total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides, CRP, TNF-α, IL-1, IL-6, and adiponectin. The dosage of the above parameters was repeated 40 days after the surgical intervention with the aim of assessing whether they showed a statistically significant change after surgery. Adiponectin levels increased significantly in both groups of patients after surgery: in patients undergoing reduction mammaplasty and abdominoplasty, the mean increase was equal to 1.68 ( P = 0.007) and 4.28 ( P = 0.019), respectively. The variation in increase was not statistically different between the 2 groups ( P = 0.254). Moreover, in the M− group, we observed that HDL levels increased and glycemia decreased significantly. Our study shows that reduction mammaplasty is a surgical procedure associated with a significant improvement in adiponectin level, HDL cholesterol level, and a significant decrease in glycemia level. The effective correlation between the role of breast adipose tissue and appearance of disease is still to be determined.